Spies among us how to stop the spies, terrorists, hackers, and criminals you don't even know you encounter every day - Winkler, Ira (Wiley Publishing, 2005)
Ira Winkler has been dubbed "A Modern Day James Bond" by CNN and other media outlets for his ability to simulate espionage attacks against many of the top companies in the world, showing how billions of dollars can disappear. This unique book is packed with the riveting, true stories and case studies of how he did it-and how people and companies can avoid falling victim to the spies among us. American corporations now lose as much as $300 billion a year to hacking, cracking, physical security breaches, and other criminal activity. Millions of people a year have their identities stolen or fall victim to other scams. In Spies Among Us, Ira Winkler reveals his security secrets, disclosing how companies and individuals can protect themselves from even the most diabolical criminals. He goes into the mindset of everyone from small-time hackers to foreign intelligence agencies to disclose cost-effective countermeasures for all types of attacks.